Entregadores de aplicativos: a rua como espaço de trabalho e trânsito de trabalhadores - Silva, Luis Henrique Alencar (2024)
On the horizon of globalized spaces, app-companies emerge as new hegemonies in the face of contemporary transformations in the world of work, especially in the face of neoliberal dramatic reforms intensified in Brazil. The purpose of this study is to analyze the relationships between app workers and the socio-spatial appropriation of the street as a workplace in order to point out the characteristics that determine the vulnerabilities of work in these spaces and their connection with digital platforms, seeking to identify the spatio-temporal reconfiguration caused by delivery apps. We use Milton Santos' theory of the urban economy two circuits to discuss this issue, with special attention to the elements that constitute the current psychosphere and their importance in the dispersion of behaviors and intentions. To this end, a biographical research approach will be used, the life story method, through socio-professional interviews with subjects who will be selected based on their experiences relating to app delivery work. The constructed data were interpreted based on thematic-categorical content analysis, inspired by the propositions of the Social Psychology of Work (SPW), seeking to analyze, based on the reports of the interviewees' working life histories, the manifestation of ideological and organizational processes that refer to the transformations in the world of work and the exploitation carried out by companies and their consequences in the dynamics of workers linked to digital platforms. The study made it possible to achieve greater depth in the issues that permeate the changes in the labor dimension, in addition to the consequences for workers with the process of uberization of work, globalization and neoliberal policies. Among the results, the spatial configuration of the app delivery worker's occupation benefits large corporations in the upper circuit, the street as a transitory place and exposure to traffic as the lack of a socio-spatial reference for work.